Proceso de atención de enfermería en paciente cesariada 25 años con infección en herida quirúrgica. - Colombatti Aguirre, Gina Paola (2021)
The nursing care process in a 25-year-old female patient with infection in a post-caesarean section surgical wound in the gynecology area of the Martin Icaza Hospital is presented below. Despite advances in modern obstetrics, puerperal infection continues to be one of the main causes of morbidity and mortality in obstetric patients, occupying 15% of maternal deaths in the world (Calderón León, 2011). Because it is a very important issue, the nursing professional must implement asepsis and antisepsis biosafety measures and prior hand washing at the time of carrying out the activities that were taught based on the nursing diagnosis and the nursing care process, according to provide direct care to the patient, in order to reduce the percentage of pathogenic microorganisms at the time of sterile wound cleaning. Therefore, the best care and care of the patient is ensured.